Fourteen years of litigation claims in cardiothoracic surgery in the United Kingdom National Health Service. Issue 9 (23rd July 2019) - Chan, Jeremy; Oo, Shwe
Abstract: Approximately 36 400 cardiac and 23 100 thoracic operations are carried out in the United Kingdom between 2006 and 2015. National Health Service (NHS) resolution, as known as the NHS litigation authority, is one of the essential bodies of the Department of Health. Its purpose is to provide NHS expertise to resolve concerns fair and square share learning for improvement. We aim to evaluate and increase awareness of medicolegal cases in cardiothoracic surgery. Total numbers and details of claims coded by NHS resolution in cardiothoracic surgery from 2004 to 2017 were requested under the Freedom of Information Act 2000. The data provided in successful claims is further breakdown into damages paid to the claimant, defence cost, claimant cost paid and the sum of the three. In contrast, unsuccessful claims only include the defence cost. Moreover, data provided also includes further analysis of primary causes and primary injuries for Claims Closed/Settled with damages paid. There were 753 claims recorded from 2004 to 2017, of which 415 (55.11%) were successful. The number of claims has been steadily increasing since 2004, with two significant raises from 2009/10 to 2010/11 (37‐55, 48.64% raise) and 2012/13 to 2013/14 (49‐69, 40.82% raise). The mean successful claim ratio was 69.58% (range, 47.56%‐ 83.33%) There is also a steady increase in the successful ratio from 2004 to 2017. In summary, this is the first study published in relation to litigation claims on cardiothoracic surgery in the United Kingdom. The results have provided insight on claims made against cardiothoracic surgery.